(untitled) (Research, Society and Development, 2022)
Objective: to discuss aspects associated with the main biomarkers used in the laboratory routine for the diagnosis of renal dysfunction in children and adolescents with DM1. Methodology: retrospective and documentary research, with descriptive procedures, through secondary data from medical records of this population in a university hospital in Paraíba. Data collection was carried out using a form containing socioeconomic, clinical and laboratory variables, and analysis was performed using SPSS software. Results and discussion: Twenty-one medical records were evaluated, obtaining a statistically significant relationship between serum potassium and urea levels (p=0.01), and high creatinine and the area of ​​residence (p=0.04). It was found that 5% of the participants had elevated creatine and urea; on urinalysis, 43% had glycosuria and had ketone bodies. Conclusion: Thus, it was found that the child and adolescent population with type 1 diabetes mellitus had alterations in biomarkers, with a mean time of diagnosis of 5.29 (±4.17) years, thus considering a probable lesion. kidney disease, as previous research has shown that these changes develop after 10 years. Furthermore, it was shown that individuals with alterations in serum creatinine also contained higher averages of potassium, glucose, SBP, DBP, HR and sodium.